Moral leadership and the Chairperson - David S Owen (Academic Chairpersons Conference Proceedings, 2017)
What does it mean for chairpersons to exercise moral leadership? This discussion will focus on clarifying what moral leadership means to chairpersons, what sorts of moral challenges are faced, and how chairpersons can exercise moral leadership.
Keywords: & #x27; academic leadership& #x27; & #x27; moral leadership& #x27; & #x27; social justice& #x27